A population‐based meta‐analysis of circulating GFAP for cognition and dementia risk. Issue 10 (3rd September 2022) - Gonzales, Mitzi M.; Wiedner, Crystal; Wang, Chen‐Pin; Liu, Qianqian; Bis, Joshua C.; Li, Zhiguang; Himali, Jayandra J.; Ghosh, Saptaparni; Thomas, Emy A.; Parent, Danielle M.; Kautz, Tiffany F.; Pase, Matthew P.; et al.
Abstract: Objective: Expression of glial fibrillary acidic protein (GFAP), a marker of reactive astrocytosis, colocalizes with neuropathology in the brain. Blood levels of GFAP have been associated with cognitive decline and dementia status. However, further examinations at a population‐based level are necessary to broaden generalizability to community settings. Methods: Circulating GFAP levels were assayed using a Simoa HD‐1 analyzer in 4338 adults without prevalent dementia from four longitudinal community‐based cohort studies. The associations between GFAP levels with general cognition, total brain volume, and hippocampal volume were evaluated with separate linear regression models in each cohort with adjustment for age, sex, education, race, diabetes, systolic blood pressure, antihypertensive medication, body mass index, apolipoprotein E ε4 status, site, and time between GFAP blood draw and the outcome. Associations with incident all‐cause and Alzheimer's disease dementia were evaluated with adjusted Cox proportional hazard models. Meta‐analysis was performed on the estimates derived from each cohort using random‐effects models. Results: Meta‐analyses indicated that higher circulating GFAP associated with lower general cognition ( ß  = −0.09, [95% confidence interval [CI]: −0.15 to −0.03], p  = 0.005), but not with total brain or hippocampal volume ( p  > 0.05). However, each standard deviation unit increase in log‐transformed GFAP levels was significantly associated with a 2.5‐fold higher risk of incident all‐cause dementia (Hazard Ratio [HR]: 2.47 (95% CI: 1.52–4.01)) and Alzheimer's disease dementia (HR: 2.54 [95% CI: 1.42–4.53]) over up to 15‐years of follow‐up. Interpretation: Results support the potential role of circulating GFAP levels for aiding dementia risk prediction and improving clinical trial stratification in community settings.